Investigation of vocational high-school students’ computer anxiety - Tuncer, Murat; Doğan, Yunus; Tanaş, Ramazan (My University, 2013)
With the advent of the computer technologies, we are increasingly encountering these technologies in every field of life. The fact that the computer technology is so much interwoven with the daily life makes it necessary to investigate certain psychological attitudes of those working with computers towards computers. As this study is limited to the impact of technology on education, anxiety, out of certain psychological attitudes, was investigated within it. The investigation was on the vocational high-school students’ computer-related anxiety, and as a data collection instrument, the Computer Anxiety Scale was used. The Computer Anxiety Scale was conducted on 265 students receiving education at various departments in the Tunceli Vocational School of Tunceli University. It was observed as a result that gender is a variable that did not make any meaningful difference for the computer anxiety, while the type of education received, grade, receiving computer education and having a computer may mean meaningful differences in terms of various sub-factors and the whole scale itself. It is necessary to determine the level of computer anxiety, and keep it under control while receiving computer education or while learning with computers.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Undergraduate study; Computer anxiety; Learning with computers; Vocational High-school students